2006
DOI: 10.3892/ijmm.17.5.869
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the kinase domain from death-associated protein kinase enhances spatial memory in mice

Abstract: Abstract. Death-associated protein kinase (DAPK) is a Ca 2+ /calmodulin-dependent serine/threonine kinase that is thought to mediate apoptosis. DAPK is highly expressed in hippocampal neurons which are essential elements for memory formation. To examine if DAPK is implicated in spatial learning and memory, both wild-type and DAPK-mutant mice were subjected to Morris water maze tests. DAPKmutant mice were generated by deleting 74 amino acids from the catalytic kinase domain of DAPK, and were used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Treatment of animals with bioavailable DAPK inhibitors results in a selective upregulation in the hippocampus of the synaptosomal scaffold protein PSD-95 (4), a marker for synaptic integrity that participates in the control of synaptic transmission and plasticity (6). Consistent with a role of DAPK in synaptic plasticity, experiments in mice showed that deletion of 74 amino acids from the catalytic domain of this kinase causes superior spatial learning compared to wild-type animals (7). These findings suggest a role for DAPK in synaptic integrity and function, but a potential DAPK substrate that is involved in such regulation has not been reported.…”
mentioning
confidence: 99%
“…Treatment of animals with bioavailable DAPK inhibitors results in a selective upregulation in the hippocampus of the synaptosomal scaffold protein PSD-95 (4), a marker for synaptic integrity that participates in the control of synaptic transmission and plasticity (6). Consistent with a role of DAPK in synaptic plasticity, experiments in mice showed that deletion of 74 amino acids from the catalytic domain of this kinase causes superior spatial learning compared to wild-type animals (7). These findings suggest a role for DAPK in synaptic integrity and function, but a potential DAPK substrate that is involved in such regulation has not been reported.…”
mentioning
confidence: 99%
“…9 Furthermore, mice with a deletion in DAPK kinase domain exhibit an enhanced spatial memory. 30 Although these studies implicate a potential impact of DAPK on AD, our finding that DAPK enhances MARK-induced tau phosphorylation and tau toxicity provides a molecular linkage of DAPK to tauopathy-related neurodegenerative disorders, such as AD. Thus, besides promoting acute neuronal cell death, elevated DAPK expression caused by genetic variation or environmental stress 1,[7][8][9] might increase the risk of AD through aberrant MARK activation.…”
Section: Discussionmentioning
confidence: 90%
“…However, the physiological functions of DAPK in vivo were not fully understood until DAPK-mutant mice were generated. Although a few studies have shown roles for DAPK in the kidney and brain (16)(17)(18)(19), the functions of DAPK in the ovary have not previously been reported. In the present study, we have clarified the tissue distributions and biocharacteristics of DAPK in the murine ovary for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Using DAPK-mutant mice lacking the 74-amino acid catalytic kinase domain of DAPK, we have revealed that DAPK plays a pro-apoptotic role in renal tubular cell apoptosis in chronic obstructive uropathy and renal ischemiareperfusion injuries (16)(17)(18). Furthermore, DAPK is involved in modulating spatial memory in mice (19). However, there have been no previous studies on the tissue distributions and physiologic functions of DAPK in female reproductive organs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation